Помогите решить, никак не пойму с чего начинать

0 голосов
30 просмотров

Помогите решить, никак не пойму с чего начинать


image

Алгебра (221 баллов) | 30 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

\sqrt[3]{1-27\sqrt[3]{26}+9\sqrt[3]{26^2}}+\sqrt[3]{26}= \\\\=\sqrt[3]{\underbrace {3^3}_{27}-\underbrace {3\cdot 3^2}_{27}\cdot \sqrt[3]{26}+\underbrace {3\cdot 3}_{9}\cdot \sqrt[3]{26}-\underbrace {(\sqrt[3]{26})^3}_{26}}+\sqrt[3]{26}=\\\\\\=\sqrt[3]{(3-\sqrt[3]{26})^3} +\sqrt[3]{26}=3- \sqrt[3]{26} +\sqrt[3]{26}=3


(a-b)^3=a^3-3a^2b+3ab^2-b^3
(835k баллов)